THE EFFECT OF TEACHING STRATEGIES AND SELF CONFIDENCE ON STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT IN AN INDONESIAN SCHOOL - Ramdha, Triana (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
In teaching writing, teaching strategy and students’ self-confidence influence students’ writing skill. The research was conducted to find out the effect of Roundtable Strategy and students’ self-confidence on students’ writing skill of descriptive text. The design of this research was quasi experimental with 2x2 factorial design. The population of this research was the VIII grade students of SMP Tri Bhakti Pekanbaru, 2015/2016 academic year. Writing test and self-confidence questionnaire were used as the research instruments. Then, the data were analyzed by using t-test formula and two ways Anova. The result of this research shows that (1) students who were taught by using Roundtable Strategy had better writing skill in writing descriptive text than those who were taught by using Three Phase Strategy. It was proven by the result of t-test which showed that tobserved was bigger than ttable, (2) students with high self-confidence who were taught by Roundtable Strategy had better writing skill in descriptive text than those who were taught by using Three Phase Strategy, (3) students with low self-confidence who were taught by Roundtable Strategy had better writing skill in descriptive text than those who were taught by using Three Phase Strategy, and (4) there was no interaction between both strategies and students’ self-confidence toward students’ writing skill, where Fobserved (0.004) was less than Ftable (3.39). In conclusion, Roundtable Strategy had a significant result on students’ writing skill than Three Phase Strategy and there was no interaction between teaching strategies and students’ self-confidence toward students’ writing skill.